2011 IEEE International Conference on Robotics and Automation 2011
DOI: 10.1109/icra.2011.5980545
|View full text |Cite
|
Sign up to set email alerts
|

Underwater source localization using an IPMC-based artificial lateral line

Abstract: Fish and aquatic amphibians use the lateral line system, consisting of arrays of hair-like neuromasts, as an important sensory organ for prey/predator detection, communication, and navigation. In this paper a novel bio-inspired artificial lateral line system is proposed for underwater robots and vehicles by exploiting the inherent sensing capability of ionic polymer-metal composites (IPMCs). Analogous to its biological counterpart, the IPMC-based lateral line processes the sensor signals through a neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…For example, they can construct a 3D view of underwater environment, rather than just having a means for velocity measurement. Some processing algorithms are developed, such as an algorithm based on the maximum likelihood estimator , an algorithm applying the adaptive beam-forming technique Nguyen et al 2008Nguyen et al , 2011Dagamseh et al 2011) and an algorithm based on artificial neural network (Abdulsadda et al 2011). Although various efforts exist, our knowledges about information processing in biological lateral line sensor systems are still limited and Object ALLFS further researches involving biology and neuroscience are still required to unveil the mystery.…”
Section: Information Processing Of Allfsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they can construct a 3D view of underwater environment, rather than just having a means for velocity measurement. Some processing algorithms are developed, such as an algorithm based on the maximum likelihood estimator , an algorithm applying the adaptive beam-forming technique Nguyen et al 2008Nguyen et al , 2011Dagamseh et al 2011) and an algorithm based on artificial neural network (Abdulsadda et al 2011). Although various efforts exist, our knowledges about information processing in biological lateral line sensor systems are still limited and Object ALLFS further researches involving biology and neuroscience are still required to unveil the mystery.…”
Section: Information Processing Of Allfsmentioning
confidence: 99%
“…A novel bio-inspired artificial lateral line system is achieved by exploiting the inherent sensing capability of ionic polymer-metal composites (IPMCs) (Abdulsadda et al 2011(Abdulsadda et al , 2012 which is shown in Fig. 14b.…”
Section: Piezoelectric and Magnetic Allfsmentioning
confidence: 99%
“…We assume that the presence of sensors has negligible effect on the flow distribution as characterized in (2), and that each sensor is able to provide a noisy measurement of the local flow velocity v along the x−direction. The latter consideration is motivated by that most beam-like flow sensors (e.g., the IPMC lateral line sensors [10], [12]) can only sense one component of the flow velocity. In the absence of noise, from (2), we get…”
Section: Problem Formulationmentioning
confidence: 99%
“…Reported signal processing schemes have included exploitation of the characteristic points (e.g., zero-crossings, maxima, etc.) in the measured velocity profile [8], matching of the measured data with pre-obtained templates [11], beamforming techniques [7], and artificial neural networks [10]. Most existing work deals with a dipole source that has fixed vibration amplitude and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…96 The curvature-sensing mechanism can also perform a scanning motion by using the electrically controlled IPMC actuator. Recently, Abdulsadda and Tan 97 reported an artificial lateral line, shown in Figure 12, based on the sensing capability of IPMCs. IPMCs are suitable for developing artificial lateral lines for several reasons.…”
Section: Ipmc Applications As Sensormentioning
confidence: 99%